Juruaudit dalaman sistem kualiti: kajian kes di Universiti Teknologi Mara, Malaysia - Khairul Anuar Mohd Ali; Nor Juliana Mohd Yusof (Penerbit ukm, 2009)

(untitled)
The purpose of this study is to investigate the involvement of academic staff in public institution of higher education (PIHE) as internal quality auditors and to determine whether duration of service as internal quality auditors and the post of academic staff differ according to fields of study. A total of 82 respondents from three different fields of study in PIHE (UiTM) have responded to the questionnaires and interview method has also been used to gain deeper understanding on the issues raised. Descriptive statistics are used to describe the level of importance of quality auditors’ roles, factors which contributed to audit effectiveness and agreement level of problems detected during audit and quality auditors’ perception towards audit process. Chi-square test is used to test significant difference among the variables. The result indicated that there were significant differences among post of academic staff and auditor’s duration of service to fields of study in PIHE. Limitations were also discussed